2020
DOI: 10.31234/osf.io/eqhfa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Open source smartphone app and tools for measuring, quantifying, and visualizing technology use

Abstract: Psychological science has spent many years attempting to understand the impact of new technology on people and society. However, the frequent use of self-report methods to quantify patterns of usage remain limited when attempting to capture subtle nuances of human-computer interaction. This has become particularly problematic for devices like smartphones that are used frequently and for a variety of purposes. While commercial apps can provide an element of objectivity, these are ‘closed’ and cannot be adapted … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…a more nuanced approach to understand both the costs and benefits of specific smartphone applications that can be monitored remotely (Geyer et al, 2020). Recent work has shown that although total time spent using smartphones had r = .16 effect sizes with anxiety and depression (matching our work), certain categories of applications have beneficial relationships (e.g., time spent reading books) (David et al, 2018).…”
Section: Choice Of Measurement Impacts Relationshipssupporting
confidence: 70%
“…a more nuanced approach to understand both the costs and benefits of specific smartphone applications that can be monitored remotely (Geyer et al, 2020). Recent work has shown that although total time spent using smartphones had r = .16 effect sizes with anxiety and depression (matching our work), certain categories of applications have beneficial relationships (e.g., time spent reading books) (David et al, 2018).…”
Section: Choice Of Measurement Impacts Relationshipssupporting
confidence: 70%
“…Our findings, however, indicate only a modest association between self-reports and usage logs, leading us to conclude that self-report measures of media use may not be a valid stand-in for more objective measures. Notwithstanding the potential biases affecting log-data 5,35,39,40 , if these measures are taken to be a valid reflection of actual usage 5,21,32,41,85 , our findings raise important concerns about the validity of findings and conclusions across many areas of the social sciences in which self-reported media use is a central outcome or explanatory variable.…”
Section: Discussionmentioning
confidence: 86%
“…23 . Data from smartphones 24,25 , online forums 26,27 , fitness trackers 28,29 or pedometers 30,31 , sociometric badges 32,33 , devices to check air quality (e.g., particulate matter) 28 Digital footprint 'The digital traces each one of us leaves behind as we conduct our lives,' 20…”
Section: Digital What?mentioning
confidence: 99%